Impact of High-Pressure Treatment on Amino Acid Profile, Fatty Acid Compositions, and Texture of Yellowfin Seabream (Acanthopagrus arabicus) Filets - Ahmed, Jasim; Habeebullah, Sabeena Farvin K.; Alagarsamy, Surendraraj; Mulla, Mehraj Z.; Thomas, Linu (Frontiers in Sustainable Food Systems, 2022)
This work describes the optimization of the pressure-time combination for the inactivation of Listeria monocytogenes in fish medium using a wide range of pressure (225-525 MPa) and holding time (5-30 min). Thereafter, the yellowfin seabream (Acanthopagrus arabicus) fillets (100 g each) were subjected to high-pressure (HP) treatment at the optimum pressure/time combination and assessed the impact of HP on the amino acid profile, fatty acid profiles, color and texture. Glycine, glutamic acid and alanine were recorded as the major amino acids, which did not change significantly after pressurization. Conversely, alanine – the leading free amino acid dropped significantly after treatment. Fatty acid analysis indicated that oleic acid and palmitic acid accounted for 29.88% and 25.59% of the total fatty acids, respectively. Pressurization did not influence the fatty acid profiles, nutritional quality indices, and hardness of yellowfin seabream fish. The color pigments of fillets, measured as a* and b* changed significantly after the treatment. Overall, the work indicates that the HP-treatment can be utilized to maintain the nutritional quality of seabream fillets; however, further research is needed to maintain the visual color of fish.